Vapor‐Fed Electrolyzers for Carbon Dioxide Reduction Using Tandem Electrocatalysts: Cuprous Oxide Coupled with Nickel‐Coordinated Nitrogen‐Doped Carbon. (11th May 2022) - Lin, Yi‐Rung; Lee, Dong Un; Tan, Shunquan; Koshy, David M.; Lin, Tiras Y.; Wang, Lei; Corral, Daniel; Avilés Acosta, Jaime E.; Zamora Zeledon, Jose A.; Beck, Victor A.; Baker, Sarah E.; Duoss, Eric B.; et al.
Abstract: Ethylene is particularly attractive due to its major importance as a feedstock for various applications including the polymer industry. As such, catalyst and electrolyzer developments are crucial to achieve industrially relevant ethylene production and efficiency levels. Here, a tandem electrocatalyst composed of copper nanocubes and nickel‐coordinated nitrogen‐doped carbon (NiNC) is presented, which is integrated into gas diffusion electrodes (GDEs) for direct conversion of vapor‐fed CO2 into ethylene. Evaluation of tandem GDEs in the vapor‐fed flow electrolyzer shows significantly increased ethylene selectivity in terms of faradaic efficiency and C2 H4 /CO ratio compared to a non‐tandem copper GDE. The enhancements are attributed to the increased local CO availability near the copper surface via effective CO2 to CO conversion on neighboring NiNC. The experimental results are validated by 3D resolved continuum simulations, which show increased flux of higher‐order products with the added CO flux from NiNC. The practical viability of Cu/NiNC catalyst is further evaluated in a membrane electrode assembly electrolyzer, achieving 40% FE toward ethylene at 150 mA cm −2 and 3.2 V. These findings highlight the high selectivity and formation rate of ethylene achieved by successful device integration of the Cu/NiNC catalyst, demonstrating the potential for implementation in large‐scale sustainable CO2 electrolyzers. Abstract : Increased ethylene formation during vapor‐fed carbon dioxide reduction is achieved by employing tandem electrocatalyst consisting of nickel‐coordinated nitrogen‐doped carbon and cuprous oxide, which act as carbon monoxide generator and coupler, respectively. Performance evaluation is conducted in both flow electrolyte and membrane electrode assembly electrolyzers to demonstrate the potential for large‐scale and direct carbon dioxide gas conversion into value‐added chemicals.